2013
DOI: 10.2298/bah1301115j
|View full text |Cite
|
Sign up to set email alerts
|

Colony strength in the spring inspection and its impact on the amount of foraged pollen at the time of red clover pollination

Abstract: In this study, the impact of honey bee colony strength in the spring inspection on the colony strength at the time of pollination, the amount of foraged pollen and on the colony strength in autumn was observed. The honey bee colonies were, after the spring inspection, divided into two groups, based on the amount of bees. The weak colonies, in spring inspection, had an average up to 4 frames occupied by bees and the strong colonies, in the spring inspection, had more than 6 frames occupied by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2014
2014

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…It is considered that red clover is one of the richest sources of isoflavones. It was found that honey bees could be excellent foragers in red clover fields, foraging an average of 98.4% of the time during peak bloom on the target crop (Jevtic et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…It is considered that red clover is one of the richest sources of isoflavones. It was found that honey bees could be excellent foragers in red clover fields, foraging an average of 98.4% of the time during peak bloom on the target crop (Jevtic et al, 2013).…”
Section: Introductionmentioning
confidence: 99%